A practical graphitic carbon nitride (g-C3N4) based fluorescence sensor for the competitive detection of trithiocyanuric acid and mercury ions. (November 2019) - Li, Meng; Wang, Bo; An, Xufei; Li, Zhiyong; Zhu, Hongtao; Mao, Boyang; Calatayud, David G.; James, Tony D.
Abstract: A fluorescent sensor for the detection of trithiocyanuric acid (TCA) and Hg 2+ was developed based on competitive interactions: non-covalent stacking between g-C3 N4 and TCA vs coordinative interaction between TCA and Hg 2+ . Electrostatic simulations were used to evaluate the interactions and help describe the detection mechanism. Moreover, normalized 2D fluorescence contour plots have been used to understand the fluorescence phenomenon. When TCA was added into a g-C3 N4 nanosheet solution free of Hg 2+, TCA interacted with g-C3 N4 nanosheets via hydrogen bonding and π-π interactions, resulting in fluorescence quenching of the g-C3 N4 nanosheets. However, upon the addition of Hg 2+, the fluorescence of the TCA-g-C3 N4 nanosheet hybrid system was restored, due to coordination of Hg 2+ with TCA through the S atoms, breaking the TCA-g-C3 N4 stacking interaction. Our results provide a new approach for the design of multifunctional nanosensors suitable for the detection of environmental pollutants. Graphical abstract: Image 1 Highlights: Graphic nitride displayed competitive fluorescence detection towards TCA and Hg 2+ . Theoretical calculations were used to evaluate the interactions and help describe the detection mechanism. Normalized 2D fluorescence contour plots have been used to understand the fluorescence phenomenon.